Accurate extraction of trap depth responsible for RTS noise in nano-MOSFETs - 马中发 张鹏 吴勇 李伟华 庄奕琪 杜磊 (Chinese physics B, 2010)
This paper presents an accurate analytical model of the random telegraph signal （RTS） noise time-constant ratio （-T/-Te） for RTS noise in nano-MOSFETs, in which the Coulomb-blockade effect on trapping and detrapping processes was taken into account. Based on this new model, the depth of the trap responsible for RTS noise in a sample n-type nano-MOSFET is extracted. The results show that large errors will be introduced to the calculated trap depth when the Coulomb-blockade effect is neglected.